2001
DOI: 10.1515/hf.2001.022
|View full text |Cite
|
Sign up to set email alerts
|

Non-Structural Carbohydrates and Catalytic Activities of Sucrose Metabolizing Enzymes in Trunks of Two Juglans Species and their Role in Heartwood Formation

Abstract: Summary In trunks of Juglans nigra and the hybrid J. major × J. regia, the presence of non-structural carbohydrates, sucrose synthesizing and degrading enzymes, and their correlation with heartwood formation was investigated. Contents of starch and sucrose were highest in the youngest sapwood, decreased with increasing age of the tissue, and were absent in the heartwood. Pools of the monosaccharides glucose and fructose were low in the sapwood, and fructose was absent from the heartwood. Glucose tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…A number of studies have provided information on distribution of protein in both deciduous and coniferous trees. The information of protein heterophyllus supported the previous investigations [5][6][7] . Abundant presence of protein droplets within xylem ray parenchyma cells indicated that the ray tissue in the secondary xylem of woody plants plays an important role in the translocation, storage, and mobilization of nutrients [17] .…”
Section: Localization Of Proteins In Phloem and Xylem Cellssupporting
confidence: 89%
See 2 more Smart Citations
“…A number of studies have provided information on distribution of protein in both deciduous and coniferous trees. The information of protein heterophyllus supported the previous investigations [5][6][7] . Abundant presence of protein droplets within xylem ray parenchyma cells indicated that the ray tissue in the secondary xylem of woody plants plays an important role in the translocation, storage, and mobilization of nutrients [17] .…”
Section: Localization Of Proteins In Phloem and Xylem Cellssupporting
confidence: 89%
“…Such types of accumulation and localization of reserve materials (e.g. starch, lipid and protein) between phloem and xylem cells is well known from extended studies on different trees [5,6,12,18] , rather than jackfruit. The results showed clearly the information of localization of reserve materials of A. heterophyllus but their intracellular localization and specific function, are still obscure.…”
Section: Localization Of Proteins In Phloem and Xylem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports of variations in levels and partitioning of storage starch granules, lipid droplets in trees, e.g. Betula pendula (Harms and Sauter 1992), Pinus sylvestris (Fischer and Höll 1992); Juglans nigra and hybrid Juglans major × J. regia (Magel et al 2001), Pinus cembra (Hoch et al 2002), Quercus petraea and Fagus sylvatica Breda 2002, Barbarous et al 2003). The data in the cited studies indicate that levels of different reserve materials from phloem to xylem provides one of the key to a full understanding of growth and development of trees.…”
Section: Introductionmentioning
confidence: 99%
“…A low temperature increases sucrose production in Arabidopsis by promoting fructose-1,6-bisphosphatase and sucrose phosphate synthase (SPS), the two key regulated enzymes in sucrose synthesis that leads to a shift in carbon partitioning to sucrose (Strand et al, 1999;Stitt and Hurry, 2002). The activity of enzymes in the sucrose synthesis pathway increases during cold acclimatization in the leaves of spinach (Martindale and Leegood, 1997), winter wheat, rye and rape (Hurry et al, 1994(Hurry et al, , 1995, and in walnut wood (Margel et al, 2001). Post-transcriptional activation of SPS occurs in potato tubers (Hill et al, 1996;Deiting et al, 1998;Krause et al, 1998), apple fruits (Duque et al, 1999) and cabbage seedlings (Sasaki et al, 2001) exposed to low temperatures.…”
Section: Discussionmentioning
confidence: 99%